2012
DOI: 10.1542/peds.2011-2736
|View full text |Cite
|
Sign up to set email alerts
|

The Human Microbiome and Its Potential Importance to Pediatrics

Abstract: The human body is home to more than 1 trillion microbes, with the gastrointestinal tract alone harboring a diverse array of commensal microbes that are believed to contribute to host nutrition, developmental regulation of intestinal angiogenesis, protection from pathogens, and development of the immune response. Recent advances in genome sequencing technologies and metagenomic analysis are providing a broader understanding of these resident microbes and highlighting differences between healthy and disease stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(206 citation statements)
references
References 146 publications
(168 reference statements)
2
199
0
5
Order By: Relevance
“…Such a disruption in appropriate colonizing bacteria leads to an alteration in phyla and less diverse individual bacterial species resulting in dysbiosis (3). A recent review article has underscored the difference in microbiota in the microbiome of children with diseases and their age-matched controls (Figure 4) (4)(5)(6). At this point, we cannot evoke the dysbiosis as a cause or as an effect of the disease.…”
Section: Dysbiosis and Disease Statesmentioning
confidence: 94%
See 1 more Smart Citation
“…Such a disruption in appropriate colonizing bacteria leads to an alteration in phyla and less diverse individual bacterial species resulting in dysbiosis (3). A recent review article has underscored the difference in microbiota in the microbiome of children with diseases and their age-matched controls (Figure 4) (4)(5)(6). At this point, we cannot evoke the dysbiosis as a cause or as an effect of the disease.…”
Section: Dysbiosis and Disease Statesmentioning
confidence: 94%
“…Improper colonization, dysbiosis (3), delays the process and results in increased susceptibility to newborn and infant infections and altered immune homeostasis leading to the expression of immune-mediated disease (4,5) and metabolic diseases (6) later in life.…”
Section: Initial Colonizationmentioning
confidence: 99%
“…4,6,7 Besides changes related to age, several other factors have been reported to alter gut microbiota community structure, including diet, birth route (vaginal versus Cesarean delivery), exposure to antibiotics, nutritional status, genetic factors, and diarrhea episodes. 2,6,8 Diarrhea episodes have been shown to be associated with an overall decrease in phylogenetic diversity. [9][10][11][12] Although modifications in the relative abundance of taxa differ by study site, studies have shown increases in the relative abundance of the phylum Proteobacteria and decreases in Bifidobacterium and Lactobacillus during diarrhea episodes.…”
Section: 3mentioning
confidence: 99%
“…Improve our knowledge of intestinal microbiome could be useful for better understanding the roles of the microbial strains in promoting infants' health [21,22].…”
Section: Discussionmentioning
confidence: 99%